A COMPREHENSIVE ANALYSIS OF ANTONYMIC RELATIONS IN ARABIC LINGUISTICS - Aadil Ramdin (International Journal of Literature and Language Studies, 2024)
antonymy, or lexical opposition, constitutes a fundamental semantic relation in human language, structuring the lexicon and facilitating complex cognitive categorizations. In Arabic linguistics, this phenomenon traditionally termed al-Taḍādd presents unique morphological, semantic, and historical dimensions that distinguish it from its counterparts in Indo-European languages. A particularly striking feature of Arabic is the existence of al-Aḍdād (auto-antonyms or contronyms), lexical items that simultaneously encapsulate a meaning and its direct opposite. This article provides a comprehensive examination of antonymy in Arabic. It traces the historical development of the concept through classical Arabic philology, categorizes antonyms using modern structural semantics, explores the unique phenomenon of al-Aḍdād, and analyzes the rhetorical application of opposition (al-Ṭibāq and al-Muqābala) in classical texts, including the Quran. By bridging classical Arabic lexicography with modern semantic theory, this paper aims to elucidate the structural elegance and semantic depth of opposition in the Arabic lexicon.